HIV-themed escape room and perceived impact on learning among undergraduate pharmacy students in a game-naïve university: A cross-sectional study - Agbo, Chinonyelum Emmanuel; Ugochukwu, Ezinwanne Jane; Isah, AbdulMuminu; Olanrewaju, Omotayo Faith; Ubaka, Chukwuemeka Michael (Currents in pharmacy teaching and learning, 2026)
This study aims to evaluate the acceptability of an HIV-themed escape room activity and the perceived impact on the learning outcomes, and knowledge of HIV management, among pharmacy students at the University of Nigeria, Nsukka. The study was conducted in three different HIV-themed escape rooms designed at the Faculty of Pharmaceutical Sciences, University of Nigeria, Nsukka (UNN), involving 36 final-year pharmacy students. The escape room activity was carried out in groups of six students, and data were collected from the participants after the activity using a 14-item questionnaire. The questionnaire was divided into three sections: socio-demographics, perception and acceptability, and feedback. Descriptive and inferential statistics were used to analyse the data. More than half of the participants (n = 20, 55.6 %) were between the ages of 20–24 years out of which a larger percentage (n = 22, 61.1 %) were females. Female participants were more likely to recommend the activity, and students with higher academic performance reported greater improvement in critical thinking skills. All teams were able to escape the room with the shortest and longest escape times recorded as 9.51 and 19.56 min, respectively. The majority of the participants (n = 34, 94.4 %) agreed or strongly agreed that the escape room activity impacted their learning. Overall, the participants reported a positive perception of the escape room activity, which also had a self-reported positive impact on their learning of HIV pharmacotherapy. This suggests that escape rooms hold promise as an innovative teaching approach in pharmacy education. •All students reported improved critical thinking skills after participating in the escape room activity.•The majority of the participants agreed that the activity positively impacted their learning of HIV pharmacotherapy.•High academic performance was associated with perceived improvement in critical thinking.•Gender influenced willingness to recommend the activity, with females more likely to recommend it.